Disentangling irregular cycles in economic time series - Dominik Schober; Oliver Woll (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
Cycles play an important role when analyzing market phenomena. In many markets, both overlaying (weekly, seasonal or business cycles) and time-varying cycles (e.g. asymmetric lengths of peak and off peak or variation of business cycle length) exist simultaneously. Identification of these market cycles is crucial and no standard detection procedure exists to disentangle them. We introduce and investigate an adaptation of an endogenous structural break test for detecting at the same time simultaneously overlaying as well as time-varying cycles. This is useful for growth or business cycle analysis as well as for analysis of complex strategic behavior and short-term dynamics.
Keywords: C22; C24; C29; O47; L50; 330; structural breaks; cluster analysis; filter; rolling regression; change points; model selection; cycles; economic dynamics